Effects of mixture of nanoparticles under different salinity in the clams Ruditapes philippinarum and Ruditapes decussatus - Costa, Paula Cristina de Oliveira (2016)
Dissertação de mestrado, Biologia Marinha, Faculdade de Ciências e Tecnologia, Universidadde do Algarve, 2015